2014
DOI: 10.5005/jp-journals-10042-1004
|View full text |Cite
|
Sign up to set email alerts
|

Trismus

Abstract: Trismus or jaw hypomobility refers to a sustained, tonic spasm of the masticatory muscles. There are various causes for this common symptom where the patient seeks medical intervention immediately, as it impairs speech and eating; causes social injunction leading to fear, anxiety and anger. Successful treatment of trismus depends on prompt recognition of its cause and immediate initiation of appropriate treatment. A thorough knowledge of this hypomobility is essential for successful treatment and to avoid perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…With the relatively low success rate of the typical single-target drug discovery paradigm in recent years, multi-target drug and network pharmacology provides a more realistic conceptual framework in both small-molecule cancer therapeutics and other drug development 2,3,14,15,[30][31][32][33] . Our study of cancer drugs revealed that multi-target pharmacology is an expected and inherent property for small-molecule therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…With the relatively low success rate of the typical single-target drug discovery paradigm in recent years, multi-target drug and network pharmacology provides a more realistic conceptual framework in both small-molecule cancer therapeutics and other drug development 2,3,14,15,[30][31][32][33] . Our study of cancer drugs revealed that multi-target pharmacology is an expected and inherent property for small-molecule therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In general, males display greater mouth opening. [2] The aetiology of trismus may be classified as follows: infection; trauma; dental treatment; temporomandibular joint disorders; tumours and oral care; drugs; radiotherapy and chemotherapy; congenital problems; miscellaneous disorders. Amongst all these causes dental treatment, specially dentoalveolar surgeries is the most common cause of trismus.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst all these causes dental treatment, specially dentoalveolar surgeries is the most common cause of trismus. [2,3] Just like pain and swelling, trismus is a post-surgical inflammatory response that involves the masticatory muscles. Overall, the complication rates post wisdom tooth surgery range from 2.6% to 30.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough review of the literature revealed a Spectrophotometric method for the quantification of Levosulpiride in bulk drug and formulation 7 . A UV method 8 for quantification in dissolution samples, HPTLC, and validated HPLC methods were reported for the simultaneous quantification of Levosulpiride with rabeprazole sodium [9][10][11][12][13] . Validated HPTLC methods were reported for the simultaneous quantification of Levosulpiride and esomeprazole in capsule dosage forms 14,15 .…”
Section: Introductionmentioning
confidence: 99%